2008
DOI: 10.3177/jnsv.54.262
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing Vitamin B6 to a Low Vitamin B6 Diet Exaggerates UVB-Induced Skin Tumorigenesis in DMBA-Treated Hairless Mice

Abstract: Summary 7,12-Dimethylbenz[ a ]anthracene (DMBA)-treated hairless mice exposed to UVB radiation were used to examine the effect of graded levels of vitamin B 6 [1, 7 or 35 mg pyridoxine (PN) HCl/kg] on skin tumorigenesis for 18 wk. Compared to the 1 mg PN HCl/kg diet, the 35 mg PN HCl/kg diet significantly elevated the incidence and multiplicity of skin tumors, while there was no difference in skin tumorigenesis between the 7 and 35 mg PN HCl/kg diets. Skin levels of oxidative stress markers (lipid peroxides an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…These problems are generally reversible when supplementation is stopped. Additionally some studies have suggested that increased levels of the B6 vitamers and some derivatives can generate toxic photoproducts as a result of UV irradiation [ 121 , 122 , 123 ].…”
Section: Vitb6 Supplements and Human Health: Is It Too Much Or Not Enmentioning
confidence: 99%
See 1 more Smart Citation
“…These problems are generally reversible when supplementation is stopped. Additionally some studies have suggested that increased levels of the B6 vitamers and some derivatives can generate toxic photoproducts as a result of UV irradiation [ 121 , 122 , 123 ].…”
Section: Vitb6 Supplements and Human Health: Is It Too Much Or Not Enmentioning
confidence: 99%
“…Studies of vitB6 supplements in cancer prevention have yielded mixed results ranging from no significant benefits seen in breast cancer to indications of protection against colorectal cancer [ 124 ]. A recent study on hairless mice given PN supplements was performed to see if increased vitB6 protected against UV-B induced skin tumors [ 121 ]. It was reasoned that vitB6 would help quench reactive oxygen species (ROS), which are associated with the development of cancer.…”
Section: Vitb6 Supplements and Human Health: Is It Too Much Or Not Enmentioning
confidence: 99%
“…Phototoxicity of B 6 -vitamers has been investigated before in the context of clinical photodermatitis and hypervitaminosis, and molecular evidence obtained from simple chemical reaction systems has been presented demonstrating the ability of B 6 -vitamers to potentiate UVA-induced photooxidation of biomolecules including DNA bases and nucleotides, amino acids and peptides, and plasmid DNA, observable at concentrations that might be relevant to phototoxicity of endogenous cutaneous B 6 -vitamers (4,(21)(22)(23)(24)(25)(26). Interestingly, it has also been observed that vitamin B 6 supplementation (using PN) enhances tumorigenesis in a hairless mouse model of UV-induced carcinogenesis (27).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has illustrated that AEDs are lifesaving, cost-effective, and easy to use by trained and untrained people. 9,[23][24][25][26]27,28 But, a nearby AED that cannot be located quickly might as well not be there at all. AED registration requirements vary by region, however, and a specific agency is not tasked with tracking and maintaining AED locations and use.…”
Section: Number Of Zipcodesmentioning
confidence: 99%